Breast conservation surgery versus total mastectomy among women with localized breast cancer in Soweto, South Africa. - Herbert Cubasch; Maureen Joffe; Paul Ruff; Donald Dietz; Evan Rosenbaum; Nivashni Murugan; Ming Tsai Chih; Oluwatosin Ayeni; Caroline Dickens; Katherine Crew; Judith S Jacobson; Alfred Neugut (PLoS ONE)
Purpose Breast conserving surgery (BCS) has become the preferred surgical option for the management of patients with nonmetastatic breast cancer in high-income countries. However, little is known about the distribution and determinants of BCS in low-and middle-income countries, especially those with high HIV prevalence. Methods We compared demographic and clinical characteristics of female patients who received BCS and those who received total mastectomy (TM) for nonmetastatic invasive carcinoma of the breast in Soweto, South Africa, 2009-2011. We also developed a multivariable logistic regression model of predictors of type of surgery. Results Of 445 patients, 354 (80%) underwent TM and 91 (20%) BCS. Of 373 patients screened for HIV, 59 (15.8%) tested positive. Eighty-two of 294 patients with stage I/II disease (28%), but just 9 of 151 (6%) with stage III disease had BCS (p<0.001). All women who received BCS (except for seven who received completion mastectomy within 6 weeks of BCS) and 235 (66.4%) women who received TM were referred for radiation therapy (RT). In our multivariable analysis, age group 50-59 years (OR = 2.28, 95% CI = 1.1-4.8) and ≥70 years (OR = 9.55, 95% CI = 2.9-31.2) vs. age group <40 years, stage at diagnosis (stage II (OR = 3.79, 95% CI = 1.6-8.2) and stage III (OR = 27.8, 95% CI = 9.0-78.8) vs. stage 1, HIV (HIV positive (OR = 3.19, 95% CI = 1.3-7.9) vs. HIV negative) and HER2-enriched subtype (OR = 3.50, 95% CI = 1.2-10.1) vs. triple negative were independently associated with TM. Conclusion TM was more common than BCS among patients with nonmetastatic breast cancer in Soweto, not only among patients with locally advanced disease at diagnosis, but also among women with stage I and II disease.